(untitled) (Psychology Travelogs, 2024)
The article investigates the main requirements for the personality of a psychologist who conducts professional psychological recruitment. The authors of the article argue that when conducting professional psychological recruitment, a psychologist receives confidential information and careless use of this information can cause problems for a person. Therefore, there are social, ethical and professional requirements for psychologists who conduct professional psychological recruitment. The authors of the article clarify the content of such concepts as ‘professional recruitment’, ‘professional psychological recruitment, ‘professional aptitude’. It is determined that professional psychological recruitment is a comprehensive study of a personality, which makes it possible to determine the degree of its psychophysiological and socio-psychological suitability for a particular activity using scientifically sound methods. Professional aptitude is defined as a characteristic that reflects a person’s ability to master a particular professional activity. The article describes the main conditions of professional psychological recruitment. The authors of the article have found that one of the important conditions for the effective functioning of the system of professional psychological recruitment is the availability of psychologists with highly developed personal qualities and professional competence. The authors of the article consider the requirements for the personality of a psychologist who conducts professional psychological recruitment. These requirements include: a psychologist’s systematic and generalised knowledge of the psyche, psychology, etc.; a diploma in psychological education; and the use of special psychological tools and psychodiagnostic techniques by a psychologist to conduct professional psychological recruitment.